2016
DOI: 10.18325/jkmr.2016.26.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Herbal Treatment for Obesity in Adults

Abstract: Objectives This systematic review is to support the effectiveness of herbal medicine for the treatment of simple obesity in adults. Methods A total of 8 electronic databases were searched in English, Chinese and Korean. Standard methodologies for the systematic review were used to search, analyze and synthesize data based on NECA's guideline for undertaking systematic review and meta-analyses for intervention. Results After screening 1781 potential articles, we identified 13 randomized controlled trials (RCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…Supportive evidence has demonstrated the safety and effectiveness of HM for obesity compared with conventional medicine. [7][8][9][10][11] However, it is also reported that some herbal formulas are associated with several adverse events (AEs), [12,13] and in some cases, the government has imposed restrictions on the use of certain medicines because of safety concerns. [14] In Korea, because of the low insurance coverage for KM obesity treatments, including prescribed HM, information, such as the prescribed medication and its AEs in real clinical practice of KM treatment for obesity are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive evidence has demonstrated the safety and effectiveness of HM for obesity compared with conventional medicine. [7][8][9][10][11] However, it is also reported that some herbal formulas are associated with several adverse events (AEs), [12,13] and in some cases, the government has imposed restrictions on the use of certain medicines because of safety concerns. [14] In Korea, because of the low insurance coverage for KM obesity treatments, including prescribed HM, information, such as the prescribed medication and its AEs in real clinical practice of KM treatment for obesity are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Korean medicine (KM) is recognized as the double axis of health care system of South Korea along with conventional western medicine. Supportive evidence has demonstrated the safety and effectiveness of HM for obesity compared with conventional medicine [7–11] . However, it is also reported that some herbal formulas are associated with several adverse events (AEs), [12,13] and in some cases, the government has imposed restrictions on the use of certain medicines because of safety concerns [14] .…”
Section: Introductionmentioning
confidence: 99%
“…한의 임상에서는 비만환자 치료 시 변증을 통 해 개인 맞춤형 치료를 시행한다는 점에서 정밀의학과 유 사한 성격을 띠고 있다 17) . 국내외에서 비만 치료에 대한 변 증 및 다양한 한약의 효과, 안전성, 부작용에 대한 기초 및 임상 연구들이 활발히 진행되어 왔다 [18][19][20][21][22] . 여러 2) 이차 유효성 평가변수…”
Section: 유전체 및 장내미생물 등 여러 요인이 복잡하게 관여unclassified
“…[ 7 ] Therefore, medical professionals and patients seek treatment with herbal medicine with few side effects as an alternative therapy for this medical challenge. [ 8 ] As this interest has increased, research on herbal medicines for obesity has been conducted in various aspects, such as drug extraction methods, [ 9 ] prescription types, [ 10 ] and dialectic methods, [ 11 ] as well as treatment effects and adverse effects. Therefore, it is becoming increasingly important to understand scientific research trends in the field of obesity and organize them systematically for more efficient research and development of treatments.…”
Section: Introductionmentioning
confidence: 99%